Virus-like infection induces human β cell dedifferentiation - Oshima, Masaya (JCI Insight, 2018)
Type 1 diabetes (T1D) is a chronic disease characterized by an autoimmune-mediated destruction of insulin-producing pancreatic β cells. Environmental factors such as viruses play an important role in the onset of T1D and interact with predisposing genes. Recent data suggest that viral infection of human islets leads to a decrease in insulin production rather than β cell death, suggesting loss of β cell identity. We undertook this study to examine whether viral infection could induce human β cell dedifferentiation. Using the functional human β cell line EndoC-βH1, we demonstrate that polyinosinic-polycytidylic acid (PolyI:C), a synthetic double-stranded RNA that mimics a byproduct of viral replication, induces a decrease in β cell–specific gene expression. In parallel with this loss, the expression of progenitor-like genes such as SOX9 was activated following PolyI:C treatment or enteroviral infection. SOX9 was induced by the NF-κB pathway and also in a paracrine non–cell-autonomous fashion through the secretion of IFN-α. Lastly, we identified SOX9 targets in human β cells as potentially new markers of dedifferentiation in T1D. These findings reveal that inflammatory signaling has clear implications in human β cell dedifferentiation.